An Internet of Things (IoT)-based aquaponics facility - Abraham, Shiny; Shahbazian, Armand; Dao, Kevin; Tran, Han; Thompson, Phillip (2017 IEEE Global Humanitarian Technology Conference (GHTC), 2017)
Aquaponics, also known as the integration of hydroponics with aquaculture, has emerged to be a successful model of sustainable food production. The symbiotic relationship between fish, plants, and bacteria, in a controlled environment, is contingent upon optimal water quality conditions. This calls for a need to develop continuous water-quality monitoring techniques that are based on intelligent data acquisition, communication, and processing. This work focuses on using Internet of Things (IoT) technology to configure and deploy smart water-quality sensors that provide remote, continuous, and real-time information of indicators related to water quality, on a graphical user interface (GUI). A sensing system comprising of a Raspberry Pi and commercial sensor circuits 1 and probes that measure Dissolved Oxygen (DO), pH, and water temperature was deployed in an aquaponics facility in a town called Manchay, near Lima, Peru 2 . Data acquired from the sensor system is uploaded to ThingSpeak 3 , an IoT analytics platform service that provides real-time data visualization and analysis. Continuous monitoring of this data, and making necessary adjustments, will facilitate the maintenance of a healthy ecosystem that is conducive to the growth of fish and plants, while utilizing about 90% less water than traditional farming.